Mind-Body Interventions, Psychological Stressors, and Quality of Life in Stroke Survivors: A Systematic Review. Issue 2 (February 2019) - Love, Mary F.; Sharrief, Anjail; Chaoul, Alejandro; Savitz, Sean; Beauchamp, Jennifer E. Sanner
Abstract : Background and Purpose—: Psychological stressors, including poststroke depression, poststroke anxiety, and posttraumatic stress disorder, are highly prevalent in stroke survivors. These symptoms exact a significant toll on stroke survivors. Clinical and research efforts in stroke recovery focus on motor disability, speech and language deficits, and cognitive dysfunction while largely neglecting psychological stressors. Evidence suggests mind-body interventions in other chronic illness populations decrease symptoms of depression, regulate immune responses, and promote resilience, yet similar studies are lacking in stroke populations. This review aims to synthesize evidence of the effects of mind-body interventions on psychological stressors, quality of life, and biological outcomes for stroke survivors. Methods—: A systematic search of PubMed, PsycINFO, and CINAHL was conducted from database inception to November 2017. Results—: Eight studies were included in the review, with a total of 292 participants. Mind-body interventions included yoga or tai chi. Of the 5 included randomized controlled trials, most were pilot or feasibility studies with small sample sizes. Psychological stressors, including poststroke depression and anxiety, along with the quality of life, improved over time, but statistically significant between-group differences were largely absent. The 3 included studies with a qualitative design reported themes reflecting improvement in psychological stressors and quality of life. No included studies reported biological outcomes. Conclusions—: Studies of mind-body interventions suggest a possible benefit on psychological stressors and quality of life; however, rigorously designed, sufficiently powered randomized controlled trials with mixed-methods design are warranted to delineate specific treatment effects of these interventions. Studies with both biological and psychological stressors as outcomes would provide evidence about interaction effects of these factors on stroke-survivor responses to mind-body interventions.